Thyroid Emphysema Following Penetrating Neck Trauma - Demet Karadağ; Egemen Doner; Baki Adapınar (Balkan Medical Journal, 2011)
Although traumatic thyroid gland rupture or hemorrhage is usually seen in goitrous glands, injuries of the normal thyroid gland after neck trauma have rarely been described in the literature. We describe a 44-year-old man who presented with thyroid emphysema and subcutaneous emphysema (SCE) that occurred after penetrating neck trauma. CT images showed complete resolution of thyroid emphysema and subcutaneous emphysema at follow-up examination. Neck injuries can be life threatening. After penetrating neck traumas, physicians should consider subtle esophageal or tracheal laceration. Thyroid emphysema can occur as the result of penetrating neck trauma. The mechanism of emphysema of the thyroid parenchyma can be explained by the thyroid gland’s presence in a single visceral compartment that encompasses the larynx, trachea and thyroid gland. We describe an unusual case of thyroid emphysema of a normal thyroid gland following a penetrating neck injury.